PEMANFAATAN BUDAYA LOKAL TERHADAP TEKNOLOGI PENANGKAPAN IKAN PADA MASYARAKAT NELAYAN Studi Kasus Di Kabupaten Pidie Jaya, Provinsi Aeeh - Faisal, Teuku Muhammad (Fakultas Ilmu Budaya Universitas Diponegoro, 2013)
In fishing communities, fishing activities are strongly influenced by local culture. The communities use heir hiowledge of local, social, cultural, religious system to labor at seas. The knowledge involves the use of technology, including charts and fishing boats which have been used for generations to survive households from poverty and vulnerability.",